Pengaruh Pengembangan Karier dan Disiplin Kerja terhadap Loyalitas Karyawan PT Catur Sentosa Adiprana Tbk. - Shifa Arinda Ramadhanty (2021)
The Effect of Career Development and Work Discipline on Employee Loyalty of Catur Sentosa Adiprana Public Company Abstract This research is using quantitative study aimed to see whether if there is an effect of career development and work discipline on the employee loyalty or not. The research object used in this study is Catur Sentosa Adiprana Public Company consisting 44 administrative or back office employees assigned to the head office, Jakarta. By using saturated sample technique, researcher obtained 44 sample units. Data recorded in this study was analyzed using validity, reliability, and R2 testing and the hipothesis was tested using t-Testing and F-Testing. Both data analysis and hypothesis testing was performed by Partial Least Square or SmartPLS 3.0 program. The results of this study indicated that (1) career development has a significant positive effect on loyalty with a t-count value of 5,096 > t-table 2,019 partially, (2) work discipline has a significant positive effect on loyalty with a t-count value of 3,216 > t-table 2,019 partially, also (3) career development and work discipline have a significant positive effect on employee loyalty with the F-count 16,428 > F-table 3,225 simultaneously. According to the results of the coefficient of determination test, namely R2 74.3%, and Adjusted R2 73%, it is true that the management of career development and good work discipline will be in line with increasing the loyalty of employees of generation X and Y at Catur Sentosa Adiprana Public Company. Keywords: Career Development, Work Discipline, and Employee Loyalty.